Haunting Words, Fluid Moods: Affect in Samuel Beckett's Mercier and Camier - Yaltir, Selvin (Istanbul Univ, Fac Letters, 2024)
Originally written in French in 1946 and translated by the author himself, Samuel Beckett's Mercier and Camier tells the story of a pseudo -couple wandering through an unnamed city. Despite the narrator's mocking tone, this quest narrative gradually reveals a search for meaning, punctuated by crises and revealed through the nonsensical dialogues between characters. By means of the disjunctions, verbal irrelevancies, and gaps in thought found in these dialogues, the narrative registers affective transitions and passages of feeling. This kind of narrative disjunction is determined, produced, and reproduced within a particularly affective milieu where social encounters become catalysts for emotional disorientation. This paper will examine how the novel's use of casual conversation explores affect's infiltration into ways of acting and speaking in everyday encounters. The novel's investment in an excessive amount of random talk solicits a host of questions around the idea of affect not only as state of mind but also as a narrative mood determining the conditions of meaningfulness. Focusing on theories of affect, I will explore the link between affective experience and verbal expression in Mercier and Camier , particularly in the absence of narrative logic and reflective coherence.
Keywords: Samuel Beckett; Mercier and Camier; affect theory; dialogue; narrative